The authoritarian personality and its relation to political apathy - Estrera, Azucena T.
This research paper is a study which aims to find out whether the level of authoritarianism of a senior student in the University of the Philippines in the Visayas would be related to his/her level of political apathy. Authoritarianism refers to the personality dimension that ranges from an authoritarian personality to the equalitarian personality. Political apathy refers to the condition of being disinterested in the political affairs of society and entails non-participation and non-involvement in such affairs., The total population was first stratified into males and females. Then, random sampling was used to get a total of 100 respondents, 50 males and 50 females. Two questionnaires were utilized to get the needed information from the respondents. One was the F-scale which is a standard test used to measure authoritarianism and the other questionnaire dealt on the political participation behaviors of the respondents. The assumption in the study is that senior students are politically apathetic because of the influence of an authoritarian family upbringing. Such an atmosphere would produce individuals who are submissive and dependent on authority figures like their parents in terms of political decisions and political behavior. So, the individual conforms to whatever his parents say. And the political apathy of such individuals is brought about by his desire to conform. The study seeks to prove the following hypotheses that: 1. Highly authoritarian students are also politically apathetic, 2. Females tend to be more authoritarian than males and as such , are more politically apathetic, 3. Highly authoritarian students came from high-income families and 4. Politically apathetic students came from low-income families. By using the correlation of coefficient (r), the study found out that the relationship between the level of authoritarianism and political apathy is either weak or non-existent (r=.0357). Males were found to be more authoritarian than females and the results show that they are also politically apathetic. A larger mean (X) was found among males than among females (M=2.9; F=2.7). This clearly shows that males tend to be more politically apathetic than females. Income level has a significant bearing on both authoritarianism and political apathy. And it was revealed that a higher level of authoritarianism and political apathy could be found among those in the high-income group than in the low-income group. Thus, there is indeed a relationship between the level of authoritarianism and level of political apathy of the respondents, however slight.